Polybenzimidazoles tethered with N-Phenyl 1,2,4-triazole units as polymer electrolytes for fuel cells - Potrekar, R. A.; Kulkarni, M. P.; Kulkarni, R. A.; Vernekar, S. P. (Journal of Polymer Science Part A-Polymer Chemistry, 2009)
Polybenzimidazole (PBI) polymers tethered with N-phenyl 1,2,4-triazole (NPT) groups were prepared from a newly synthesized aromatic diacid, 3'-(4-phenyl-4H-1,2,4-triazole-3,5-diyl) dibenzoic acid (PTDBA). The obtained polymers show superior thermal and chemical stability and good solubility in many aprotic solvents. The inherent viscosities of all polymers were around 1 dL/g. They exhibit high thermal stability with initial decomposition temperature ranging from 515 to 530 degrees C, high glass transition temperature ranging from 375 to 410 degrees C, and good mechanical properties with tensile stress in the range of 66-98 MPa and modulus 1897-2600 MPa. XRD analysis indicates that these polymers are amorphous in nature. PhysicochemiCal properties such as water and phosphoric acid-uptake, oxidative stability, and proton conductivity of membranes of these polymers have also been determined. The proton conductivity ranged from 4.7 x 10(-3) to 1.8 x 10(-2) S cm(-1) at 175 degrees C in dry conditions. (C) 2009 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 47: 2289-2303, 2009
Keywords: fuel cells; Polybenzimidazole; synthesis and characterization; Triazole

Variation in acid moiety of polybenzimidazoles: investigation of physico-chemical properties towards their applicability as proton exchange and gas separation membrane materials - Kumbharkar, S. C.; Islam, Md. Nazrul; Potrekar, R. A.; Kharul, Ulhas K. (Polymer, 2009)
A series of polybenzimidazoles (PBIs) were prepared from 3,3'-diaminobenzidine (DAB) and substituted aromatic dicarboxylic acids. Effects of added polarity, bulk and isomerism in the dicarboxylic acid moiety on the properties of formed aromatic polybenzimidazoles were investigated. Solution polycondensation procedure was optimized for individual case of PBI synthesis in order to obtain inherent viscosity of >= 1 dL/g. Analysis of physical properties, water uptake, acid doping (H(3)PO(4) and H(2)SO(4)) and gas permeability was performed. All these PBIs exhibited high thermal stability, good solvent solubility and amorphous nature. The uptake of H(3)PO(4) varied from 9 to 20.1 moles per repeat unit (mol/RU), H(2)SO(4) uptake varied from 3.39 to 3.81 mol/RU, while water uptake varied from 1.8 to 3.6 mol/RU of PBI. The dibromoterephthalic acid and tert-butylisophthalic acid based PBI showed the highest H(3)PO(4) uptake in the series, while tert-butylisophthalic acid based PBI exhibited the highest water uptake. Acid uptake was correlated with swelling of the PBI matrix, while density estimation of H(3)PO(4)-doped PBI by He gas expansion method could be correlated to the physical state of PBI. 5-tert-Butylisophthalic acid and 4,4'-(hexafluoroisopropylidene)bis(benzoic acid) based PBI exhibited higher H(2) and O(2) permeability than other PBIs. The ideal gas selectivity for O(2)/H(2) was considerably higher for most of the PBIs than conventional gas separation membrane materials. These analyses suggested that some of these PBIs have a potential to be used as a PEM or gas separation membrane material. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Gas permeability; Polybenzimidazole; Proton exchange membrane